PERANCANGAN APLIKASI GO-LOUNDRY MENGGUNAKAN DART BERBASIS ANDROID - Kasianus Kalfinus Nduru; Suharyanto, Cosmas (Computer Science and Industrial Engineering, 2022)
Clothing is useful for protecting and protecting from the heat of the sun, smog, and other objects that can irritate the skin. However, a healthy body requires clean, fragrant and neat clothes, to have them all, we must wash the clothes we will use. R&R Tayloor With Assyifa Londry is one of the MSME businesses founded by shop owner Mrs. Dew who specializes in washing clothes, carpets, shoes, dolls and the like in washing machines. As for the problems experienced by customers where receipts or notes are sometimes lost and wet, the second problem is that the laundry business owner does not have customers anymore, so for this problem the researcher wants to find a solution by designing an Android - London-based Go Application that can be used by customers and shop owners to Manage laundry orders. The Android-based Go - laundry application is the result of a project that with this Android-based laundry ordering application allows customers to easily place laundry orders and can save electronic records stored in the Go - Londonry application, reducing customer anxiety if the Londonry owner's paper print is lost or wet. The benefits that R& Tayloor has with Assyifa Londry are attracting more customers than before, increasing transaction value and maintaining customer loyalty for R&R Tayloor with Assyifa Londry. In this design the researcher uses the darts programming language with a framework to facilitate the design of the researcher's Go-londry application. The test method used in the study is the black box test, the black box test is the AR screen test to make it easier to use.